1989
DOI: 10.1063/1.343471
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally agile far-infrared detector using an n-i-p-i superlattice

Abstract: Schematic band diagram of an n-p doped slIperlattice for three different states. (a) Ground state; (b) with some electrons and holes extracted; and (c) with charge carners injected.956

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ruden [189] discussed using a homogeneously doped nipi (ie not £-doped) to reduce the (effective) bandgap of InSb to the 10 pm range. Ruden's calculations considered tunelling assisted interband absorption (Franz-Keldysh effect [169]).…”
Section: Sawtooth Superlattice Infrared Detectorsmentioning
confidence: 99%
“…Ruden [189] discussed using a homogeneously doped nipi (ie not £-doped) to reduce the (effective) bandgap of InSb to the 10 pm range. Ruden's calculations considered tunelling assisted interband absorption (Franz-Keldysh effect [169]).…”
Section: Sawtooth Superlattice Infrared Detectorsmentioning
confidence: 99%
“…It was suggested that the reduced effective bandgap of a nipi could be used to extend the IR response of interband detectors such as InSb to longer wavelength[189,167].…”
mentioning
confidence: 99%